2014
DOI: 10.1037/a0035356
|View full text |Cite
|
Sign up to set email alerts
|

Test of a potential causal influence of earlier age of gambling initiation on gambling involvement and disorder: A multilevel discordant twin design.

Abstract: The premise that an association between an earlier age of gambling initiation and the later development of disordered gambling is causal has not yet been empirically examined. The current study used a multi-level discordant twin design to examine the nature of this association. Participants were 3,546 same-sex twins (mean age = 37.7 years) from the Australian Twin Registry who completed a telephone interview that included an extensive assessment of gambling and related behaviors. Multilevel models were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…We examined whether there were differences between men and women in the age that they first gambled, the time until they gambled regularly for the first time, the time until they experienced the first symptom of DG, and the time until the first onset of a DG diagnosis. Building on previous research demonstrating that an early age of gambling initiation 1719 , type of gambling activity 20 , and co-occurring psychiatric disorder 18,20–21 are associated with an increased risk of developing DG, we also examined whether these factors would predict a shorter time to the onset of gambling disorder and potentially account for any observed gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…We examined whether there were differences between men and women in the age that they first gambled, the time until they gambled regularly for the first time, the time until they experienced the first symptom of DG, and the time until the first onset of a DG diagnosis. Building on previous research demonstrating that an early age of gambling initiation 1719 , type of gambling activity 20 , and co-occurring psychiatric disorder 18,20–21 are associated with an increased risk of developing DG, we also examined whether these factors would predict a shorter time to the onset of gambling disorder and potentially account for any observed gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…One investigation found that gambling behaviors were significantly more heritable in young men than young women (Beaver et al, 2010), whereas another found no sex differences in genetic and environmental influences in a young adult twin sample (Blanco, Myers, & Kendler, 2012). A follow-up study of the same sample suggested that there was no evidence for sex differences in the genetic and environmental influences on gambling etiology and family environmental factors explained individual differences in gambling involvement (Slutske & Richmond-Rakerd, 2014). An adolescent twin study by Winters and Rich (2003) failed to find any effects of genetic factors on girls’ gambling behaviors compared to a significant influence of genetics on boys’ gambling, suggesting a sex difference in etiology.…”
mentioning
confidence: 99%
“…Second, data on many of the independent variables in our study were self-reported and may possibly be inaccurate such as when asked about age at first smartphone use, time spent and reason for using smartphone during a weekday. Third, other factors known to associate with younger age at first use and the development of smartphone addiction were not controlled for, such as particular individual personality characteristics like impulsivity (Dalbudak & Evren, 2014;Kim et al, 2015), disruptive behavior problem (Dalbudak & Evren, 2014;Slutske et al, 2014), and family environment (Slutske et al, 2014).…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Orsal, Orsal, Unsal, & Ozalp (2013) found internet addiction median scores to be significantly higher in those who started internet use at an earlier age (≤9 vs. 10-12 vs. ≥13 years) in Turkish university students (n=3442, mean age=17.6 years). Slutske et al (2014) revealed an inverse association between earlier age of initiation of gambling during childhood and adolescence and the likelihood of gambling disorder in adulthood. Sahin, Ozdemir, Unsal, & Temiz (2013) showed problematic mobile phone use to be statistically significantly associated with younger age at first mobile phone use (≤13 vs. ≥16 years) in Turkish university students (n=576, mean age= 20.8 years).…”
mentioning
confidence: 99%